Pendekatan POP-SDM (pemodelan dan optimasi sumber daya manajemen) dalam penguatan komitmen organisasional guru - Siwi Puji Astuti; Sri Setyaningsih; Dian Wulandari (Universitas Indraprasta PGRI, 2025)
The purpose of this study is to examine both the direct and indirect effects of the independent variables psychological empowerment, authentic leadership, and interpersonal communication on teachers’ organizational commitment, with pedagogical competence serving as the intervening variable. This research employed a mixed-methods approach, combining qualitative and quantitative methods using SEM-PLS and SITOREM analysis. The study sample consisted of 160 teachers from 15 schools located in 5 sub-districts within East Jakarta Region 2. The research instruments included five tools: four questionnaires and one test instrument for assessing pedagogical competence. The results of the study revealed significant direct effects, with six hypotheses accepted and one rejected. Regarding indirect effects, two hypotheses were accepted and one was rejected. Through SITOREM analysis, 15 indicators were identified as needing improvement, prioritized by urgency, while 9 indicators were recommended to be maintained or further developed